GLASS PLATES FOR MOTOR VEHICLES AND OTHER MEANS OF TRANSPORT - Camelia CĂPĂŢÎNĂ; Gheorghe Gamaneci (Fiabilitate şi Durabilitate)
At present, the majority of high quality glass plate is used in vehicle industry. The paper presents the technological process for obtaining glass plate, used in vehicle industry. Besides the usual attributes of high quality plane glass, those used in vehicle industry must not result in sharp and cutting splinters when broken, being dangerous for the passengers. This quality, due to which it is called safety glass, is obtained by various methods.